1991
DOI: 10.1148/radiology.181.2.1924788
|View full text |Cite
|
Sign up to set email alerts
|

Perfluoroctylbromide as a gastrointestinal contrast agent for MR imaging: use with and without glucagon.

Abstract: The utility of perfluoroctylbromide (PFOB) as a gastrointestinal contrast agent for magnetic resonance (MR) imaging was evaluated with MR examinations performed in 30 subjects (16 healthy volunteers and 14 patients). Transaxial T1-, proton density-, and T2-weighted MR images were acquired in each subject before and after the administration of PFOB. The healthy volunteers each underwent two sets of post-PFOB MR examinations, one before and one after glucagon administration. The degree of bowel marking, clarity … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
28
2

Year Published

1993
1993
2002
2002

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 63 publications
(30 citation statements)
references
References 0 publications
0
28
2
Order By: Relevance
“…Although not all MR examinations require luminal contrast material, in many instances the use of an oral contrast agent increases the detection of disease, as well as the confidence of the diagnostic radiologist in distinguishing normal from abnormal. Development of potential agents has included work with materials that either increase or decrease the signal intensity of the intestinal lumen [1][2][3][4][5][6][7][8][9][10]. Regardless of the type of contrast material utilized, the major goal has been to design agents that demonstrate complete and uniform marking of the intestinal lumen, while assuring patient acceptance and safety.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Although not all MR examinations require luminal contrast material, in many instances the use of an oral contrast agent increases the detection of disease, as well as the confidence of the diagnostic radiologist in distinguishing normal from abnormal. Development of potential agents has included work with materials that either increase or decrease the signal intensity of the intestinal lumen [1][2][3][4][5][6][7][8][9][10]. Regardless of the type of contrast material utilized, the major goal has been to design agents that demonstrate complete and uniform marking of the intestinal lumen, while assuring patient acceptance and safety.…”
Section: Discussionmentioning
confidence: 99%
“…Utilization of magnetic resonance (MR) imaging in the pediatric abdomen has been hindered by the lack of an ideal gastrointestinal contrast agent [1,2]. Shortcomings result from the inability to reliably differentiate bowel from adjacent structures.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Although very fast imaging will diminish these artifacts, a more general approach to overcome this limitation is the use of negative bowel contrast agents combined with the administration of hypotonic drugs. Different drugs have been analyzed for pharmacological motion suppression [1][2][3][4][5]. In a previous study [2], we demonstrated that oral dicyclomine significantly reduces the noise associated with the movement of the gastrointestinal tract in MR images.…”
mentioning
confidence: 98%
“…When negative MR bowel contrast agents were employed, investigators have found that peristalsis-related artifacts did not present a problem [4][5][6][7]. However, pharmacological motion suppression with glucagon has successfully been used to image the bowel wall after oral administration of the diamagnetic negative contrast agent perfluoroctylbromide (PFOB) [8,9]. The present study at 1.5 T was undertaken to evaluate the impact of anticholinergic hyoscine butylbromide upon motion artifacts, visualization of the bowel wall, and lesion delineation on T1-weighted SE images before and after oral administration of the negative bowel contrast agent oral magnetic particles (OMP) [Abdoscan, Ferristene (USAN), Nycomed Imaging AS, Oslo, Norway].…”
mentioning
confidence: 99%